(3fXe GdeYdheGJ GdeMGSHjI aj Jbjje GdeTQhYGJ GdESJKeGQjIs - (3KfGA eMeO(B, (3WYjeIs ((3GdGScfOQjI(B:s (3GJQGc ddfTQ hGdJhRjY(B,s, 2003)
(3eGgjI GdeTQhYGJ GdESJKeGQjI GdQCSeGdjI(B- (3CgejI GSJNOGe GdeYdheGJ GdeMGSHjI hGdJMdjd Gdcej(B- (3Jbjje GdeTQhYGJ GdESJKeGQjI GdQCSeGdjI(B- (3GdHjGfGJ hGdeYdheGJ GdeMGSHjI GddGReI dJNWjW GdeTQhYGJ GdESJKeGQjI GdQCSeGdjI(B- (3Jbjje GdeTQhYGJ GdESJKeGQjI(B- (3JMdjd EVGaj dWQb Jbjje GdeTQhYGJ GdESJKeGQjI GdQCSeGdjI(B- (3Jbjje GdeTQhYGJ GdESJKeGQjI GdQCSeGdjI aj XQha GdeNGWQI hYOe GdJCcOs
Keywords: (3GdeMGSHIs; (3GdeTQhYGJ(B- (3GdESJKeGQs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s